(untitled) (Journal of Asian Development Studies, 2015)
The winding up of the MDGs in September 2015 as elicited the proposal for SDGs which in all likelihood will be adopted at the 70th session of the UN General Assembly. The achievement of MDGs has generated mixed reactions from stakeholders and there is a growing consensus for an improvement in the goals and targets for the post-MDGs. In order to have a comprehensive goals and targets that will meet the development aspirations of developing countries, this paper evaluates the methodological accuracy for the inclusion of political, social, economic and environmental goals to give a fresh perspective for the adoption of sustainable development goals (SDGs). The analysis shows that the developing regions that performed unimpressive on the MDGs are also fraught with poor ratings in good governance indicators (SSA, SAS and MENA) while other regions (LAC, EAC and EAP) that performed creditably well also exhibited good ratings in good governance indicators. Using robust linear regression, findings show that good governance indicators (political stability, rule of law, control of corruption and accountability) and socioeconomic factors have an impact on GDP per capita suggesting that political, economic and social factors are critically important for achieving economic development. In the final submission, a maximum of 10 goals and 70 targets are adequate for the adoption of SDGs.